Health, Nutrition and human resource development: a crucial link - Akhter, Sanzida; Wohab, Md. Abdul (BRAC University, 2010)
Health and nutrition is one of the important components of human resource development. The relationship between health-nutrition and human resource development is reciprocal and takes a cyclical fashion. The first section of this paper endeavors to establish a link between health, nutrition and human resource development. The second section discusses this linkage in the context of Bangladesh and with the particular focus on its health and nutrition policies and programs.